MicroRNA 26a targets Ezh2 to regulate apoptosis in mouse ovarian granulosa cells. (4th May 2021) - Huo, Shiwei; Qi, Hongrong; Si, Yuexiu; Li, Changzhou; Du, Wenyan
ABSTRACT: In the mammalian ovary, <1% of the follicles ovulate, with most undergoing degenerative atresia during ovarian follicular development. Follicular atresia is caused by the apoptosis of granulosa cells (GCs), although the precise underpinning mechanism remains unidentified. MiR-26a regulates various cellular events, including cell division, apoptotic signaling, and cell differentiation, migration, and autophagy. Here, we demonstrated that miR-26a regulated apoptosis in GCs in the mouse ovary through Ezh2, a key regulator of GC viability. We also found that transcription of miR-26a changed in response to an LH antagonist and a GnRH agonist. In addition, miR-26a transcription was downregulated following LH-induced transition of GCs to granulosa-lutein cells (GLCs). Dual-luciferase reporter assays confirmed Ezh2 as a miR-26a target. Exogenous expression in GCs of miR-26a mimics resulted in decreased Ezh2 expression, while miR-26a inhibition in GCs induced the opposite phenotype. Ezh2 silencing additionally reduced the anti-apoptotic effect of miR-26a inhibition in GCs. These data highlight the critical role of miR-26a in targeting Ezh2 and regulating apoptosis in mouse ovarian GCs. Abbreviations: GC: Granulosa cell; GLCs: Granulosa-lutein cells; LH: Luteinizing hormone; miRNA: MicroRNA; NC: Negative control; Cyt-c: Cytochrome c; GnRH: Gonadotropin releasing hormone; i.p.: intraperitoneal injection; cKO: conditional knock-out; WB: Western blotting; hCG: Human chorionic gonadotropin; NPC: nasopharyngeal carcinoma.